2018
DOI: 10.1186/s13019-018-0797-3
|View full text |Cite
|
Sign up to set email alerts
|

Skeletonized internal thoracic artery harvesting: a low thermal damage electrosurgical device provides improved endothelial layer and tendency to better integrity of the vessel wall compared to conventional electrosurgery

Abstract: BackgroundElectrosurgery is fundamental to the precise, fast and bloodless preparation of internal thoracic artery grafts in cardiac surgery. The PEAK PlasmaBlade is a monopolar electrosurgical device that uses pulsed radiofrequency energy to generate a plasma-mediated discharge along an insulated electrode, creating a cutting edge while the blade stays near body temperature. The aim of this study is to compare the histological samples, cardiac computed-tomography of graft patency, and clinical outcomes of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The use of the PlasmaBlade in cardiac surgery is very limited. A recent study published on PlasmaBlade-assisted internal mammary artery harvesting showed non-inferiority of the PlasmaBlade compared to conventional electrocautery when considering the 6-month patency of the internal mammary arteries ( 7 ). Another recently published trial on the safety of using the PlasmaBlade for pocket preparation for ICD device insertion or generator change in patients on anticoagulation has shown significantly reduced adverse events compared to standard electrocautery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of the PlasmaBlade in cardiac surgery is very limited. A recent study published on PlasmaBlade-assisted internal mammary artery harvesting showed non-inferiority of the PlasmaBlade compared to conventional electrocautery when considering the 6-month patency of the internal mammary arteries ( 7 ). Another recently published trial on the safety of using the PlasmaBlade for pocket preparation for ICD device insertion or generator change in patients on anticoagulation has shown significantly reduced adverse events compared to standard electrocautery.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma is an electrically conductive cloud created when the energy contacts tissue. The “plasma” allows the radiofrequency energy to cross the tissue at a much lower overall power level, resulting in lower operating temperatures and less thermal damage ( 7 ). The PlasmaBlade operates at 40–100°C, while the blade tip stays near body temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PB is a relatively new electrosurgical technology developed to achieve cutting and coagulation effects with a relatively low operating temperature, which reduces thermal damage (6,25). It applies high-frequency RF pulses to generate electrical plasma along the edge of the electrode (26).…”
Section: Discussionmentioning
confidence: 99%
“…The internal mammary artery endothelium possesses a number of properties that make it resistant to the development of atherosclerosis [25]. Current data recommend skeletonised internal mammary artery harvesting for revascularisation, with low thermal damage providing an improved endothelial layer and better integrity of the vessel wall [26]. IMA graft failure most commonly results from damage during mobilisation or harvesting, spasm, inflammation or suboptimal target vessel anastomosis [22].…”
Section: Discussionmentioning
confidence: 99%